The therapeutic potential of deubiquitinating enzyme inhibitors. (19th January 2010) - Colland, Frédéric
Abstract : Proteases play a key role in various pathological processes and several protease inhibitors are already available for treatment. DUBs (deubiquitinating enzymes) constitute one of the largest classes of human proteases and are key effectors of the ubiquitin–proteasome system. This pathway regulating cellular protein turnover has been implicated in the pathogenesis of many human diseases, including neurodegenerative disorders, viral diseases and cancer. The therapeutic efficacy of the proteasome inhibitor Velcade® (bortezomib) for treating multiple myeloma and mantle cell lymphoma establishes this system as a valid target for cancer treatment. A promising alternative to targeting the proteasome itself would be to target the upstream, ubiquitin conjugation/deconjugation system, to generate more specific, less toxic anticancer agents. Advances in small molecule-based inhibitors specifically targeting DUBs are presented in this review.